Pemanfaatan Tanaman Dalam Kehidupan Spiritual Umat Hindu di Bali (Perspektif Pendidikan Lingkungan Hidup) - Sudarsana, I Ketut; Surya Santha, I Made (Jayapangus Press, 2024)
Development carried out in Bali, where people's livelihoods depend on agriculture, plantations, and tourism, must prioritize the Balinese cultural side, which is based on Hindu spiritual teachings. It is essential to pay attention to the teachings in Bali, as they are the basis for Bali's sustainable development. One of these teachings is the Tri Hita Karana teaching, especially in the weakening section. This weakening concept teaches humans to maintain a harmonious relationship between humans and the nature around them, which is related to human survival. The aim of the research is to describe the use of plants in the spiritual life of Hindus in Bali. The method used is qualitative research with library data collection techniques. The research results show that Balinese people are very close to the environment, especially plants that complement ceremonies or rituals. These plants are an inseparable part of the spiritual life of the Balinese people, considering that these plants act as materials for religious services and healing and provide educational teachings related to environmental conservation.